Pengaruh Peningkatan Kadar Asam Urat Dengan Derajat Keparahan Stenosis Arteri Koroner Pada Penderita Sindrom Koroner Kronik - Defyna Lestari; Budi Satrijo (Jurnal Klinik dan Riset Kesehatan, 2026)
Coronary artery disease (CAD) remains the most common cause of death globally despite advancements in treatment. Uric acid (UA) has been associated with the development of cardiovascular events in patients with Chronic Coronary Syndrome (CCS). Several hypotheses suggest that UA exerts a negative impact on coronary arteries and/or increases the risk of major adverse cardiovascular events (MACE).